Scarf osteotomy or Mau osteotomy for correction of moderate to severe hallux valgus deformity: a prospective, randomized study - Avcu, Bülent; Akalın, Yavuz; Çevik, Nazan; Öztürk, Alpaslan; Şahin, Namık; Öztaş, Savaş; Özkan, Yüksel (The European Research Journal, 2018)
Objective. The aim of this study was to compare the clinical and radiological results of Mau osteotomy and Scarf osteotomy with a modified McBride procedure to patients with moderate to severe hallux valgus deformity. Methods. The study included 40 feet which patients were separated into 2 groups followed up for 5 months. Scarf osteotomy was applied to 20 patients including 16 females and 4 males (Scarf group)) and a Mau osteotomy to 20 patients including 17 females and 3 males (Mau group). Radiological measurements were taken preoperative, postoperative and at the final follow-up examination of the hallux valgus angle (HVA), intermetatarsal angle (IMA), distal metatarsal articular angle (DMAA), metatarsocuneiform angle (MCA), the 1st metatarsophalangeal joint congruity, 1st metatarsal length, fibular sesamoid subluxation rate. Clinical evaluation was made according to the American Orthopaedic Foot and Ankle Society (AOFAS) and the severity of pain was assessed with the visual analog scale (VAS). Results. There was no difference between the groups in term of the mean HVA, IMA, MCA and DMAA values in preoperative and postoperative measurements. A significant improvement was determined in all the angle values in Scarf and Mau group (p < 0.001). A significant increase in DMAA and shortening in the metatarsal length were determined in Mau group compared to Scarf group (p < 0.001). An improvement in joint congruity was seen in the goups (p < 0.001). There was a significant improvement in term of the AOFAS and VAS values in the groups (p < 0.001). Conclusion. Scarf and Mau osteotomies can provide the desired level of improvement in the short-term follow-up results of moderate to severe hallux valgus deformity, taking into consideration the clinical importance that complications are not formed.